Bank Muamalat's Strategy of Branch Office of Tulungagung Regency in Facing Non Performing Financing - Wahyu Nurhayati, Dwi Astuti; Oktavia, Novi Tri (Department of Islamic Banking, 2024)
This study aimed at describing the strategy utilized by the Bank Muamalat Branch Office of Tuluangung regency to face problem financing. To address this concern, the researchers used a qualitative approach in the form of field research to conduct this study. In addition, observation, interviews, and documentation were used to collect data. According to the findings of this study, Bank Muamalat Branch Office of Tulungagung Regency's strategy for managing problem financing entails first contacting the customer to learn firsthand what circumstances are preventing him from making timely installment payments. The subsequent phase is intensive invoicing. The Bank will send a Statement Letter to the costomer if he fails to comply with his obligations. The Bank then carries out Restructuring by means of the three R's: Rescheduling, Reconditioning, and Restructuring. If a customer is unable to pay his loan obligations to the bank, the bank executes the customer's collateral.